Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Exactly like the previous question you posted.
-3x² - 9x = 0
Divide each side of the equation by -3 :
x² + 3x = 0
Factor the left side:
x (x + 3) = 0
This is true if x=0 or if x=-3 .
-3x² - 9x = 0
Divide each side of the equation by -3 :
x² + 3x = 0
Factor the left side:
x (x + 3) = 0
This is true if x=0 or if x=-3 .
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.